BEATS IN THE HELICOPTER RADIO CHANNEL OF ONE-BAND SIGNAL - Ivanov, Volodymyr; Zadorozhniy, Alexander; Myakishev, Ilya (Proceedings of National Aviation University (archive), 2019)
The frequency distortion of a one-way signal at the output of a non-directional antenna helicopter, which arises during rotation of the helicopter main rotor, is detected. The power loss of a useful signal for the existence of satellites is appreciated. They arise in near each spectral component of a useful signal. In this case, they exist due to the energy of a useful signal. Therefore, the signal/noise ratio at the output of the non-directional antenna of the helicopter becomes lower than at its input. Reducing the power of a useful signal will result in a corresponding deterioration in the quality of the radio communication.